2018
DOI: 10.1155/2018/1260325
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Autonomous 5-D Hyperjerk RC Circuit with Hyperbolic Sine Function

Abstract: A novel autonomous 5-D hyperjerk RC circuit with hyperbolic sine function is proposed in this paper. Compared to some existing 5-D systems like the 5-D Sprott B system, the 5-D Lorentz, and the Lorentz-like systems, the new system is the simplest 5-D system with complex dynamics reported to date. Its simplicity mainly relies on its nonlinear part which is synthetized using only two semiconductor diodes. The system displays only one equilibrium point and can exhibit both periodic and chaotic dynamical behavior.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Figure 2 provides four views of the 5-D Hyperjerk chaotic attractor where the stable equilibrium point is shown as a red dot. that a point attractor coexists with a strange attractor [27,28]. This is further clarified later in the next section.…”
Section: Bifurcations and Multistabilitymentioning
confidence: 74%
See 1 more Smart Citation
“…Figure 2 provides four views of the 5-D Hyperjerk chaotic attractor where the stable equilibrium point is shown as a red dot. that a point attractor coexists with a strange attractor [27,28]. This is further clarified later in the next section.…”
Section: Bifurcations and Multistabilitymentioning
confidence: 74%
“…As the real parts of the correlated eigen values are always negatively valued; the equilibrium is stable for the entire region of system parameters. For instance, if we set b = 3; a 0 = 1.5; a 1 = 3; a 2 = 2; a 3 = 1; a 4 = 1; l 1 = 1; l 2 = 2.6 then its eigen values can be calculated as: λ 1 = − 0.1194 + 2.5677i; λ 2 = − 0.1194 − 2.5677i; λ 3 = − 0.8425 + 0.0000i λ 4 = − 0.2094 + 0.7036i; λ 5 = − 0.2094 − 0.7036i (3) It is a general conclusion that since the equilibrium point is always stable, it can be predicted that a point attractor coexists with a strange attractor [27,28]. This is further clarified later in the next section.…”
Section: Fixed Point and Stabilitymentioning
confidence: 99%
“…Symmetry always plays an important role in physical system. This property is found in a variety of system including nonlinear and chaotic systems [30][31][32][33][34][35][36][37][38][39][40]. Symmetric chaotic systems provide the possibility to observe coexisting attractors.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, good interest has been devoted to the finding of both jerk and hyperjerk systems in the chaos literature (Vaidyanathan et al, 2018a;Vaidyanathan, 2017;Vaidyanathan, 2016El-Nabulsi, 2018;Prousalis et al, 2018;Ahmad and Srisuchinwong, 2018;Tsafack and Kengne, 2018;Daltzis et al, 2018;Vaidyanathan et al, 2018b;Wang et al, 2017). Vaidyanathan et al (2018a) reported a new chaotic jerk system with two quadratic nonlinearities and discussed its applications to electronic circuit implementation and image encryption.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmad and Srisuchinwong (2018) reported a 4-D hyperjerk system with hyperchaos and having no rest point. Tsafack and Kengne (2018) reported a 5-D hyperjerk system with circuit design. Daltzis et al (2018) reported a 4-D hyperjerk system with hyperchaos and built a real circuit design for the hyperjerk system.…”
Section: Introductionmentioning
confidence: 99%